Discrete Element Method Simulation and Experimental Validation of Pattern Development in a Rotating Drum Mixer. Issue 8 (23rd May 2018) - Barczi, Tomas; Kohout, Martin; Kozakovic, Martin; Havlica, Jaromir; Ratnayake, Chandana
Abstract: The handling and processing of powders and granular materials can be crucial for the quality of a final product. Therefore, a detailed description and analysis of granular flow phenomena from first principles is very valuable. In the present study, simulations of granular mixing and segregation of binary‐sized mixtures using a discrete element method were performed for horizontal rotating drum mixers. Numerical results were compared with experimental measurements and significant agreement between both approaches was found. The development of specific flow patterns was observed. The formation of these complex spatiotemporal patterns is influenced by the size of the mixer, the aspect ratio of length to diameter, the rotational speed of the drum, and the initial distribution of the particles. Abstract : The quality of granular mixing has great importance in many applications. Herein, simulations of granular mixing and segregation of binary‐sized mixtures using a discrete element method were performed for horizontal rotating drum mixers. The formation of axially segregated bands relative to operating conditions, drum dimensions, and the initial distributions of particles was analyzed.